Optimization of electroporation and other non‐viral gene delivery strategies for T cells. (1st September 2020) - Harris, Emily; Elmer, Jacob J.
Abstract: CAR‐T therapy is a particularly effective treatment for some types of cancer that uses retroviruses to deliver the gene for a chimeric antigen receptor (CAR) to a patient's T cells ex vivo. The CAR enables the T cells to bind and eradicate cells with a specific surface marker (e.g., CD19 + B cells) after they are transfused back into the patient. This treatment was proven to be particularly effective in treating non‐Hodgkin's lymphoma (NHL) and acute lymphoblastic leukemia (ALL), but the current CAR‐T cell manufacturing process has a few significant drawbacks. For example, while lentiviral and gammaretroviral transduction are both relatively effective, the process of producing viral vectors is time‐consuming and costly. Additionally, patients must undergo follow up appointments for several years to monitor them for any unanticipated side effects associated with the virus. Therefore, several studies have endeavored to find alternative non‐viral gene delivery methods that are less expensive, more precise, simple, and safe. This review focuses on the current state of the most promising non‐viral gene delivery techniques, including electroporation and transfection with cationic polymers or lipids.